Development and validation of a new analytical method based on UV-visible spectroscopy for quantification of ceftaroline fosamil in powder for injection - Machioli, Lilian F.; Rosa, Gabriele C.; Carlos, Graciela; Mendez, Andreas Sebastian Loureiro (Drug Analytical Research, 2026)
Quantification of drugs is an essential part for ensuring quality, safety and efficacy of pharmaceutical formulations. For this, validated methods must be used in order to guarantee analytical reliability during monitoring in clinical studies and quality control. In the present study, we aim to develop a reliable, accurate, accessible and rapid UV-VIS spectrophotometry method for quantification of ceftaroline fosamil in powder for intravenous administration. Each analyzed solution was prepared individually and the only reagent used was Milli-Q water, as a solvent, making the method eco-friendly. The absorbances were measured at 242 nm, the peak absorbance found for the drug. The developed method was validated according to ICH and ANVISA guidelines, proving to be specific and demonstrating good linearity in the concentration range of 5 μg.mL-1 to 15 μg.mL-1, with determination (r2) and correlation coefficients (r) equal to 0.9999. The limits of detection and quantification found were acceptable (0.51 μg.mL-1 and 1.55 μg.mL-1, respectively). The method exhibited excellent intermediate precision and repeatability, with relative standard deviation values of 0.87% and 0.98%, respectively. Furthermore, the method’s accuracy was confirmed, showing a mean recovery of 100 ± 2.67%. Additionally, the robustness was assayed and confirmed using Plackett-Burmann design. In conclusion, the method can easily be applied for routine quality control analysis.